If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + 3) + 3x = 12 Reorder the terms: -2(3 + x) + 3x = 12 (3 * -2 + x * -2) + 3x = 12 (-6 + -2x) + 3x = 12 Combine like terms: -2x + 3x = 1x -6 + 1x = 12 Solving -6 + 1x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 1x = 12 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = 12 + 6 1x = 12 + 6 Combine like terms: 12 + 6 = 18 1x = 18 Divide each side by '1'. x = 18 Simplifying x = 18
| 2x^2=-12x-7 | | 5x+x-5=5x+2 | | a^3-63=0 | | y-x=2 | | 6x^2+38x+28=0 | | 4x-(9x+6)=5x-26 | | z-5z=8z-1-z | | 25a^2-120a+144=0 | | 81z^2-36z+4=0 | | 8x^8-64x^7+16x^6=0 | | -x+7=19 | | 6x+4y=160 | | -6y-1(8y-9)=7+2(3-y) | | 4z^2-20z+25=0 | | 4x+2(6)=26 | | 2x^3-9x^2+3x+5=0 | | 5(x-5)=x | | 1x+22=2 | | 4x+5(x-1)=6 | | 4x^2+3y=37 | | 0.5(m+4)=3(m-1) | | 3(c-2)=2(c-6) | | 8x-2(x+1)=2(3x-1) | | 4-t=3(t-1)-5 | | 2(b+1)-(3+b)=-3 | | (6Y+7)-(5+5y)=10 | | 5+(x-5)=x | | 16y-112+8y=4y-150 | | 3x-y=19 | | 1.7q-5.1-4.1q=-1.4Q-5.1 | | 11-2m-(-13+2n)= | | 11-2m(-13+2n)= |